The Impact of Self Reminder Interactive (SRI) Application on Quality of Life, Compliance of anti-TB Drug, and Self Efficacy Among TB Patients - Sriningsih, Sriningsih; Mendrofa, Fery Agusman Motuho; Sonhaji, Sonhaji (Yayasan Ahmad Mansyur Nasirah, 2024)
The impact of technology plays a significant role in health, including prevention and rehabilitation of Tuberculosis patients. One of the breakthroughs made to reduce pulmonary tuberculosis sufferers is through telenursing to improve patient behavior in preventing transmission of pulmonary tuberculosis. This study aimed to identify the influence of the Community Resources-based SRI (Self Reminder Interaction) Application on improving the quality of life, anti-TB drug Compliance, and Self-Efficacy among Pulmonary Tuberculosis patients. This study is a quasi-experiment research type with a nonequivalent control pre-test and post-test design. The sample in this study was selected using simple random sampling with a total of 50 respondents. The independent variables of this study were SRI application implementation, then the dependent variables included quality of life, self-efficacy, and anti-TB drug adherence. The results of this study consist of the majority of respondents were aged 35 to 39 years old, female, and working as private laborers. The bivariate results found the significant impact of SRI application to increase quality of life, self-efficacy, and anti-TB drug adherence after. Among case groups, there is found significant improvement between pre and post-test after giving intervention. It can be concluded that the SRI application is significant in improving TB patient life. Future studies could add more predictors related to the accessibility of technology such as education level, income, and place of residence to explore the impact of such application in multivariate analysis.